Meta-analysis of changes in thiol-disulfide homeostasis during preeclampsia - Dan Wang; Guihong Yang; Xinxin You; Zijuan Zhang (Biomolecules & Biomedicine, 2024)
The present study systematically assessed alterations in thiol-disulfide homeostasis among women with preeclampsia (PE) through meta-analysis. This was conducted as such changes are believed to be associated with the oxidative stress underlying this condition. A comprehensive search of Medline, Web of Science, and Embase databases was conducted from their inception until 22 March 2023, to identify studies comparing levels of native thiol, total thiol, and disulfide between pregnant women with PE and those without PE. Results were pooled using a random-effects model to account for study heterogeneity. The analysis included a total of 631 women diagnosed with PE and 668 healthy pregnant women, encompassing 13 case-control studies and 1 prospective study. Pooled outcomes revealed that women with PE had significantly lower blood levels of native thiol, (mean difference [MD] -51.42 umol/L; 95% confidence interval [CI] -79.75 to -23.10 umol/L; P < 0.001; I2 = 0%) and total thiol (MD -65.56 umol/L; 95% CI -104.97 to -26.15 umol/L; P = 0.001; I2 = 0%) compared to the control group. In contrast, no significant difference was observed in blood disulfide levels between the two groups (MD -1.10 umol/L; 95% CI -4.41 to -2.21 umol/L; P = 0.51; I2 = 0%). Subgroup analyses indicated that the results were consistent across studies matched by gestational age and body mass index, as well as those with varying quality scores (P for subgroup differences all > 0.05). In conclusion, women with PE are associated with significantly reduced blood levels of native and total thiols but show no change in blood disulfide levels, suggesting a state of reduced antioxidants in PE.